2020
DOI: 10.1007/978-3-030-58465-8_5
|View full text |Cite
|
Sign up to set email alerts
|

GazeRoomLock: Using Gaze and Head-Pose to Improve the Usability and Observation Resistance of 3D Passwords in Virtual Reality

Abstract: Authentication has become an important component of Immersive Virtual Reality (IVR) applications, such as virtual shopping stores, social networks, and games. Recent work showed that compared to traditional graphical and alphanumeric passwords, a more promising form of passwords for IVR is 3D passwords. This work evaluates four multimodal techniques for entering 3D passwords in IVR that consist of multiple virtual objects selected in succession. Namely, we compare eye gaze and head pose for pointing, and dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…74 1. Attackers' confidence together with their notably low successful attack rate on eye gaze is inline with prior work that emphasises the high resistance to observations of gaze-based authentication [28,46,61,68]. When comparing attackers' confidence between the two study types, we found a significant three-way interaction effect (input method × threat model × study type), F 1.399,47.582 = 10.485, p<0.05.…”
Section: Attackers' Confidencesupporting
confidence: 84%
“…74 1. Attackers' confidence together with their notably low successful attack rate on eye gaze is inline with prior work that emphasises the high resistance to observations of gaze-based authentication [28,46,61,68]. When comparing attackers' confidence between the two study types, we found a significant three-way interaction effect (input method × threat model × study type), F 1.399,47.582 = 10.485, p<0.05.…”
Section: Attackers' Confidencesupporting
confidence: 84%
“…In order to demonstrate the potential of existing authentication mechanisms in terms of usability and security, George et al [88] carried on their work in [86] and investigated the effect of pointing and selection choices on usability and security for 3D passwords in VR. They presented GazeRoomLock, an authentication mechanism similar to RoomLock [86] that leverages other interaction modalities instead of only using HHC.…”
Section: Knowledge-based Authenticationmentioning
confidence: 99%
“…Boutros et al [98][99][100][101][102] and periocular images captured by HMDn while taking into consideration the low source dataset (OpenEDS, captured using approaches, they concluded that iris and vice use might be utilized for biometric ed a lightweight and precise segmentation by HMDs and benchmarked many wellapproaches in terms of sample size effect aches resulted in encouraging results, with 6% for periocular verification. nvestigations tested in real-world use-case chieved by both the segmentation and [88] 2021 GazeRoomLock ctors referring to something you ARE or (gait). Primarily, biometric data of any kind cal traits in the human body, such as a sical biometrics has been researched in hold.…”
Section: Knowledge-based Authenticationmentioning
confidence: 99%
“…It also maintains the user's space around the table by detecting who enters and leaves the space at what time and accordingly adjusting the content display. GazeRoomLock [72] combines gaze and head pose for user authentication in VR applications. EyeVeri [224] applies signal processing and pattern matching techniques to explore conscious and unconscious gaze patterns for access authentication.…”
Section: Control and Interactionmentioning
confidence: 99%